A sea of tentacles: optically discernible traits resolved from planktonic organisms in situ. (3rd August 2019) - Ohman, Mark D
Abstract: Trait-based simplifications of plankton community structure require accurate assessment of trait values as expressed in situ . Yet planktonic organisms live suspended in a fluid medium and often bear elongate appendages, delicate feeding structures, and mucous houses that are badly damaged upon capture or removal from the fluid environment. Fixatives further distort organisms. In situ imaging of zooplankton from a fully autonomous Zooglider reveals a suite of trait characteristics that often differ markedly from those inferred from conventionally sampled plankton. In situ images show fragile feeding appendages in natural hunting postures, including reticulate networks of rhizopods, feeding tentacles of cnidarians, and tentilla of ctenophores; defensive spines and setae of copepods; intact mucous houses of appendicularians; and other structures that are not discernible in conventionally collected zooplankton. Postures characteristic of dormant copepods can be identified and the presence of egg sacs detected. Intact, elongate diatom chains that are much longer than measured in sampled specimens are resolvable in situ . The ability to image marine snow, as well as small-scale fluid deformations, reveals micro-habitat structure that may alter organismal behaviour. Trait-based representations of planktonic organisms in biogeochemical cycles need to consider naturally occurring traits expressed by freely suspended planktonic organisms in situ .